Multiple myeloma: five-year experience at a University Hospital - Juliana Todaro; Jandey Bigonha; Davimar Miranda Maciel Borducchi; Leandro Luongo Matos; Damila Cristina Trufelli; Suzane Martines Alves de Sales; Marina Rampazzo Del Valhe Shiroma; Auro del Giglio (Einstein (São Paulo), 2011)
Objective: To present a descriptive analysis of patients diagnosedwith multiple myeloma, correlating it with mortality. Methods: Aretrospective study that analyzed consecutive patients diagnosedwith multiple myeloma under follow-up at the Faculdade deMedicina do ABC from 2006 to 2010. Results: The median agewas 58.5 years. Anemia was observed upon diagnosis in 87%of patients, hypercalcemia in 38%, and creatinine levels higherthan 2 mg/dL in 19%. M protein was detected in 85.7%. Thefive-year survival rate was 74.6%. Multivariate analysis showedstatistical significance for Durie-Salmon staging (p = 0.037). TheInternational Staging System and immunoglobulin type did notcorrelate significantly with survival of the group. Conclusion: Thisset of cases from a tertiary public healthcare service reflect theapproach of multiple myeloma in a predominantly young populationwith advanced clinical staging, with results comparable to thoseof the literature.